BACE1 Is Necessary for Experience-Dependent Homeostatic Synaptic Plasticity in Visual Cortex. (13th May 2014) - Petrus, Emily; Lee, Hey-Kyoung
Abstract : Alzheimer's disease (AD) is the most common form of age-related dementia, which is thought to result from overproduction and/or reduced clearance of amyloid-beta (A β ) peptides. Studies over the past few decades suggest that A β is produced in an activity-dependent manner and has physiological relevance to normal brain functions. Similarly, physiological functions for β - and γ -secretases, the two key enzymes that produce A β by sequentially processing the amyloid precursor protein (APP), have been discovered over recent years. In particular, activity-dependent production of A β has been suggested to play a role in homeostatic regulation of excitatory synaptic function. There is accumulating evidence that activity-dependent immediate early gene Arc is an activity "sensor, " which acts upstream of A β production and triggers AMPA receptor endocytosis to homeostatically downregulate the strength of excitatory synaptic transmission. We previously reported that Arc is critical for sensory experience-dependent homeostatic reduction of excitatory synaptic transmission in the superficial layers of visual cortex. Here we demonstrate that mice lacking the major neuronal β -secretase, BACE1, exhibit a similar phenotype: stronger basal excitatory synaptic transmission and failure to adapt to changes in visual experience. Our results indicate that BACE1 plays an essential role in sensory experience-dependent homeostatic synaptic plasticity in the neocortex.